2010
DOI: 10.3897/compcytogen.v4i2.45
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of mitochondrial COI and nuclear ribosomal ITS2 in the Culex pipiens complex and in Culex torrentium (Diptera: Culicidae)

Abstract: Abstract. Polymorphism of the mtDNA gene COI encoding cytochrome C oxidase subunit I was studied in the mosquitoes Culex pipiens Linnaeus, 1758 and C. torrentium Martini, 1925 from sixteen locations in Russia and in three laboratory strains of subtropical subspecies of the C. pipiens complex. Representatives of this complex are characterized by a high ecological plasticity and there are signifi cant ecophysiological differences between its morphologically similar members. The full-size DNA sequence of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…Extended study of exon 1 of the gene tim revealed 4 DNA haplotypes in Culex pipiens f.molestus and 19 haplotypes in Culex pipiens f.pipiens. Decrease in DNA variability for the underground mosquitoes of Culex pipiens f.molestus was also reported earlier in our study of mitochondrial DNA (Shaikevich and Zakharov 2010). …”
Section: Discussionsupporting
confidence: 84%
“…Extended study of exon 1 of the gene tim revealed 4 DNA haplotypes in Culex pipiens f.molestus and 19 haplotypes in Culex pipiens f.pipiens. Decrease in DNA variability for the underground mosquitoes of Culex pipiens f.molestus was also reported earlier in our study of mitochondrial DNA (Shaikevich and Zakharov 2010). …”
Section: Discussionsupporting
confidence: 84%
“…The ITS2 region was amplified using primers complementary to the 5,8S and 28S rRNA [20]. The DNA extraction and PCR were performed according to previously described methods [18].…”
Section: A Albopictusmentioning
confidence: 99%
“…PCR amplification of the COI gene was performed using the primers TY-J-1460 [17] and COIR2 [18]. The mosquitoes were tested for Wolbachia infection using PCR with primers wsp81F and wsp691R complementary to the gene wsp [19].…”
Section: A Albopictusmentioning
confidence: 99%
“…The diagnostic utility of 5′ COI mtDNA and ITS2 rDNA assays in molestus/pipiens delimitation Sequence-based molecular approaches to Cx. p. pipiens ecotype designation predominantly used 5′ end of cytochrome c oxidase subunit I mtDNA (5′ COI mtDNA) as a DNA barcode marker (Shaikevich, 2007(Shaikevich, , 2017Shaikevich & Zakharov, 2010;Danabalan et al, 2012;Gunay et al, 2015). This locus was firstly proposed by Shaikevich (2007) as diagnostic for molestus/pipiens delimitation when underground, autogenous populations in a European part of Russia were found to differ in one fixed substitution from aboveground, anautogenous populations (HII vs. HI labeled herein, respectively).…”
Section: Discussionmentioning
confidence: 99%